An Ode to ODA against all Odds? A Novel Game-Theoretical and Empirical Reappraisal of the Terrorism-Aid Nexus - Elkhan Richard Sadik-Zada (Atlantic Economic Journal, 2021)
The present inquiry revisits the influence of the fourth religious wave of modern terrorism on the allocation of official development assistance (ODA). The theoretical framework is predicated first on comprehensive review of the pertinent literature on the nexus between political instability and foreign aid, augmented by the assessment of Central Intelligence Agency declassified documents and Congressional Service Reports. Based on the systematic review of the sources, the study puts forward a novel dynamic differential game theory model, which enables derivation of the scenarios for foreign aid allocation. The study finds that despite dominance of geopolitical and/or commercial interests in the allocation of aid, high incidence of terrorist attacks does not lead to less development aid, but rather catalyzes it. Subsequent empirical analysis of a dataset with 121 developing and transition economies spanning between 1970 and 2016 reveals that terrorism incidents, level of political rights, and the War on Terror had a statistically significant positive long-run and negative short-run effect on the level of foreign aid commitment of the Organisation for Economic Co-Operation and Development member states. The growth rate of foreign aid in the developing countries with a predominantly Muslim population has been systematically 0.1 to 0.85 percent greater than in non-Muslim countries. Subsequent assessment of the security bias in the allocation of aid indicates that re-securitization of aid since 1998 has led to weak diversion of aid commitment from areas with fewer terrorism incidents to jurisdictions with a greater frequency of terrorist attacks.
Keywords: D72; D73; L72; O13; 330; Official development assistance; Terrorism incidents; Securitization; War on Terror; Pooled mean group; Nonparametric panel approach; Open-loop Nash equilibrium